(untitled) (Herald of Journalism, 2020)
The article gives a complete picture of the pension system at pres ent stage of development of Kazakhstan. Reform of the pension system is primarily focused on its further development, increase the level of pension provision the most disadvantaged sectors of the population and improve the economic stability of the country. Feature of the reformwas the fact that accumulative system was introduced not as anadditional, as well as the basic element of nongovernmental pension. The specific figures shows the ascending order pension accruals over the past years, and a positive development of the system, compared with other countries of independent states.